(untitled) (Research, Society and Development, 2021)
Introduction: The Mayaro virus (MAYV) is an arbovirus belonging to the Togaviridae family of the alphavirus genus, which is transmitted by hematophagous arthropods to vertebrate hosts, whereas non-human primates are considered primary reservoirs. Objective: To evaluate the expression of messenger RNAs (mRNA) of crucial proteins in the microRNA pathway and inflammatory cytokines in human cells during infection by the MAYV. Materials and Methods: Viral samples propagated in RD cell cultures. The RNAs were collected and extracted at predetermined times. The total RNA was then used to detect mRNA by PCR in real time (qRT-PCR). Results: the Mayaro virus RNA was verified in the cells during all the days of infection. The AgR2 mRNA protein dropped sharply by 2 dpi and 3 dpi. Conclusion: The present study demonstrated the reduction of proteins in infection with the Mayaro virus.